Catalytic Electrosynthesis of N, O‐Heterocycles – Recent Advances. Issue 14 (21st February 2020) - Listratova, Anna V.; Sbei, Najoua; Voskressensky, Leonid G.
Abstract : Recognized as gentler and more environmentally friendly compared to conventional methods, catalytic electrochemical reactions are a powerful tool for constructing heterocycles. Of special interest is indirect electrolysis, where the use of a redox mediator provides an additional means of reaction control, thus avoiding over‐oxidation and facilitating improved selectivity. This minireview describes recent advances in catalytic electrochemical reactions for synthesizing N, O ‐heterocycles that appeared from 2018 until September 2019. Abstract : This minireview focuses on recent achievements in employing of indirect electrolysis in the construction of N‐, O ‐heterocycles published from 2018 until September 2019. The electrochemical approaches are classified in accordance with the type of catalyst and presented as two sections: metal‐catalyzed electrosynthesis reactions and non‐metal‐catalyzed electrosynthesis reactions.